Predictability modulates pronunciation variants through speech planning effects: A case study on coronal stop realizations. Issue 1 (10th June 2020) - Kilbourn-Ceron, Oriana; Clayards, Meghan; Wagner, Michael
Predictability has been shown to be associated with many dimensions of variation in speech, including durational variation and variable omission of segments. However, the mechanism or mechanisms that underlie these effects are still unclear. This paper presents data on a new aspect of predictability in speech, namely how it affects allophonic variation. We examine two coronal stop allophones in English, flap and glottal stop, and find that their relationship with predictability is quite different from what is expected under current theories of probabilistic reduction in speech. Flapping is more likely when the word that follows is more predictable, but is not influenced by the frequency of the word itself, while glottal stops are more likely in words that are less predictable. We propose that the crucial distinction between these two allophones is how they are conditioned by phonological context. This, we argue, interacts with online speech planning processes and gives rise to variability for context-dependent allophones. This hypothesis offers a specific, testable mechanism for certain predictability effects, and has the potential to extend to other factors that contribute to variability in speech.